Psychological and support interventions to reduce levels of stress, anxiety or depression on women’s subsequent pregnancy with a history of miscarriage: an empty systematic review - San Lazaro Campillo, Indra (BMJ Open, 2017)
OBJECTIVE: The aim of this systematic review was to assess the effect of interventions to reduce stress in pregnant women with a history of miscarriage. DESIGN: A systematic review of randomised controlled trials (RCTs). DATA SOURCE: A total of 13 medical, psychological and social electronic databases were searched from January 1995 to April 2016 including PUBMED, CENTRAL, Web of Science and EMBASE. ELIGIBILITY CRITERIA: This review focused on women in their subsequent pregnancy following miscarriage. All published RCTs which assessed the effect of non-medical interventions such as counselling or support interventions on psychological and mental health outcomes such as stress, anxiety or depression when compared with a control group were included. Stress, anxiety or depression had to be measured at least preintervention and postintervention. RESULTS: This systematic review found no RCT which met our initial inclusion criteria. Of the 4140 titles screened, 17 RCTs were identified. All of them were excluded. One RCT, which implemented a caring-based intervention, included pregnant women in their subsequent pregnancy; however, miscarriage was analysed as a composite variable among other pregnancy losses such as stillbirth and neonatal death. Levels of perceived stress were measured by four RCTs. Different types of non-medical interventions, time of follow-up and small sample sizes were found. CONCLUSION: Cohort studies and RCTs in non-pregnant women suggest that support and psychological interventions may improve pregnant women’s psychological well-being after miscarriage. This improvement may reduce adverse pregnancy-related outcomes in subsequent pregnancies. However, this review found no RCTs which met our criteria. There is a need for targeted RCTs that can provide reliable and conclusive results to determine effective interventions for this vulnerable group.